Multiple dimensions of healthcare management of leprosy and challenges to its elimination - Cavalcante, Marília Daniella Machado Araújo; Larocca, Liliana Müller; Chaves, Maria Marta Nolasco (Revista da Escola de Enfermagem da USP, 2020)
To analyze assistance provided to people affected by leprosy through multiple dimensions of Care Management. Method Exploratory single case study with a mixed methods approach conducted at a referral service in a Southern Brazil municipality. Content analysis and webQDA software were used for data treatment. Results Participants included health professionals, people with leprosy and their family members. leprosy incidence was found to indicate its dissemination in the study setting, despite its low endemicity. Predominance of multibacillary cases and diagnoses with grade 2 disability indicate shortcomings in early detection efficacy. Contradictions were found in multiple dimensions of Care Management, leading to the understanding that the challenges in fighting leprosy are not only biological, but also socially determined. Conclusion The presented challenges demonstrate the health care network’s frailty regarding lowering this disease’s rate and the need for effective public policies to confront diseases that, similarly to leprosy, are determined by social inequality.